A vivência da santidade nos dias atuais à luz da Lumen Gentium - Ferreira, Fábio Luiz (2022)
The present work, through the bibliographic research, aims to present a study on the experience of holiness nowadays at the light of the universal call contained in the chapter V of the Dogmatic Constitution Lumen Gentium, having as a point of reference the figure of the Father and the experience of a filial spirituality. Holiness is a God’s atribute, it is takes part of God's nature, and he is the source of all holiness. To man holiness is only possible by participation. In the Church everyone is called to the fullness of the christian life, regardless of the assumed state of life. God addresses the human being, relates to him and wants to make every human person take part of the divine life and joins him through the Son. We are children in the Son and the grace of divine sonship makes us participants of divine life. By baptism we are adopted as God’s children and inserted int Christ’s mystical body which is the Church. The Contemporary man must walk a path of rescue of his identity of God’s child and let the Holy Spirit, who moves hearts, lead it to a filial relationship with the Father, who calls each of his children to be saint, as he is Holy, it means a holiness committed to humanity, committed to others and which is lived in the simplicity of everyday human life